Effect of Blend-Pelleted Products Based on Carinata Meal or Canola Meal in Combination with Lignosulfonate on Ruminal Degradation and Fermentation Characteristics, Intestinal Digestion, and Feed Milk Value When Fed to Dairy Cows - Aya Ismael; Basim Refat; Victor Hugo Guevara-Oquendo; Peiqiang Yu (Dairy, 2023)
The objectives of this study were to investigate the effect of newly developed blend-pelleted products based on carinata meal (BPPCR) or canola meal (BPPCN) in combination with peas and lignosulfonate on ruminal fermentation characteristics, degradation kinetics, intestinal digestion and feed milk values (FMV) when fed to high-producing dairy cows. Three dietary treatments were Control = control diet (common barley-based diet in western Canada); BPPCR = basal diet supplemented with 12.3%DM BPPCR (carinata meal 71.4% + pea 23.8% + lignosulfonate4.8%DM), and BPPCN = basal diet supplemented with 13.3%DM BPPCN (canola meal 71.4% + pea 23.8% + lignosulfonate 4.8%DM). In the whole project, nine mid-lactating Holstein cows (body weight, 679 ± 124 kg; days in milk, 96 ± 22) were used in a triplicated 3 × 3 Latin square study for an animal production performance study. For this fermentation and degradation kinetics study, the experiment was a 3 × 3 Latin square design with three different dietary treatments in three different periods with three available multiparous fistulated Holstein cows. The results showed that the control diet was higher (p < 0.05) in total VFA rumen concentration (138 mmol/L) than BPPCN. There was no dietary effect (p > 0.10) on the concentration of rumen ammonia and ruminal degradation kinetics of dietary nutrients. There was no significant differences (p > 0.10) among diets on the intestinal digestion of nutrients and metabolizable protein. Similarly, the feed milk values (FMV) were not affected (p > 0.10) by diets. In conclusion, the blend-pelleted products based on carinata meal for a new co-product from the bio-fuel processing industry was equal to the pelleted products based on conventional canola meal for high producing dairy cattle.